2007
DOI: 10.1007/s11060-007-9478-0
|View full text |Cite
|
Sign up to set email alerts
|

Autologous hematopoietic stem cell transplantation for high-risk brain tumors in children

Abstract: Autologous hematopoietic stem cell transplant (AHSCT) has been advocated as a form of salvage therapy for children with high-risk or relapsed brain tumors but only limited data are available currently. We report the outcomes of pediatric brain tumors treated with AHSCT in a quaternary referral center in Hong Kong over 10 years (June 1996-May 2006). Thirteen patients with medulloblastoma (n = 9), cerebral primitive neuroectodermal tumor (n = 1), ependymoma (n = 1), germ cell tumor (n = 1) and cerebellar rhabdoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 25 publications
5
24
1
1
Order By: Relevance
“…Valteau-Couanet et al (16) described two long-term survivors in a group of 15 children receiving an intensive regimen with busulfan and thiotepa, plus surgery and re-irradiation in a nonspecified subgroup. Similarly, Cheuk et al reported only one survivor of recurrent medulloblastoma of 5 patients given CSI at diagnosis, after treatment with high-dose chemotherapy including thiotepa, etoposide, and carboplatin with PBSC rescue (17). Of the children with these same features treated at St. Jude's, Shih et al mention only one survivor treated for recurrent pineoblastoma of a total of 15 children with relapsing medulloblastoma/ primitive neuroecto dermal tumor given a variety of high-dose regimens (18).…”
Section: Discussionmentioning
confidence: 99%
“…Valteau-Couanet et al (16) described two long-term survivors in a group of 15 children receiving an intensive regimen with busulfan and thiotepa, plus surgery and re-irradiation in a nonspecified subgroup. Similarly, Cheuk et al reported only one survivor of recurrent medulloblastoma of 5 patients given CSI at diagnosis, after treatment with high-dose chemotherapy including thiotepa, etoposide, and carboplatin with PBSC rescue (17). Of the children with these same features treated at St. Jude's, Shih et al mention only one survivor treated for recurrent pineoblastoma of a total of 15 children with relapsing medulloblastoma/ primitive neuroecto dermal tumor given a variety of high-dose regimens (18).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to "high-grade" gliomas and ependymomas, AHSCT is known to achieve better results in recurrent, refractory or high-risk medulloblastomas, primitive neuroectodermal tumours of the brain, atypical teratoid rhaboid tumours and germinomas of the central nervous system with disease-free survival of 10-50% [16][17][18]. Nevertheless, dose-dependant therapeutic response of tumours of neuroectodermal origin that was previously reported in these studies did not manifest in our results [2,[19][20][21]. We also observed poor results in rhabdomyosarcoma patients.…”
Section: Discussionmentioning
confidence: 47%
“…For example, patients rely on autologous hematopoietic stem cell transplantation to replenish immune capacity against recurrent cancer after surgery and chemotherapy [49] . Currently, 240 studies on "stem cell therapy of cancer" exist in mostly Phases and specificity; and (3) The vehicle possesses the ability to home in on targets.…”
Section: Clinical Trials Show Discrepanciesmentioning
confidence: 99%